The New Characteristics of Crimes that Undermine Market Economy Order and Regulation in Criminal Law - Wang, Linlin (International Journal of Social Sciences and Public Administration, 2024)
Chapter 3 of the Criminal Law of the People's Republic of China makes specific provisions for acts that undermine market economy order. However, with the development of society and economy, some new types of acts that undermine market economy order have emerged in market economic activities. These acts either have new subjects or new means and tools, or have new objectives, which seriously undermine market economy order and cause property losses to the state and people. Perfecting the criminal law regulation of these new types of acts is crucial for maintaining a regulatory system for undermining socialist market economy order.